Health Related Quality Of Life Amongst People Affected By Leprosy In South Ghana: A Needs Assessment - Bello, A.I.; Dengzee, S.A.; Iyor, F.T. (Leprosy Review, 2013)
Aim: This study examined Health Related Quality of Life (HRQOL) among leprosy-affected elderly people at three leprosoria located in South Ghana. Methods: Seventy elderly people who have been cured of leprosy but were undergoing socio-economic rehabilitation at three selected Leprosaria in the southern part of Ghana, were involved in this study. They comprised 31 female and 39 male adults with leprosy-related residual impairment and disability. The main outcome measure was a standardised HRQOL questionaire which comprised physical functioning, role functioning, social functioning, cognitive functioning, health perception and pain. Descriptive statistics of mean and standard deviation were used to summarize the data whilst relationships and comparisons among and between the variables were evaluated using linear regression analysis and independent t-test respectively. Alpha level was set at P , 0·05. Results: The mean age of the participants was 59·7 ^ 13·5 years. The overall mean score of the subjects (40·9 ^ 7·6) on the six domains of the questionnaire was below average. The highest and lowest mean scores were obtained in social functioning (56·9 ^ 20·1) and physical functioning (15·0 ^ 25·1) domains respectively. All the domains were significantly and positively correlated (P , 0·05) with the overall HRQOLscores.Agehadnosignificant relationship (P . 0·05) on any of the domains and the overall HRQOL scores. Male participants scored signicantly higher (P , 0·05) than their female peer on cognitive functioning and HRQOL. Conclusion and implication: This study demonstrated low QOL among the sampled elderly people affected by leprosy at the selected leprosoria, thus stressing the need for measures that could improve their health and socio-economic status within the settlements.
Research Article
Keywords: South Ghana; leprosy; quality of life